Multimedia elements of digital storytelling for Dyslexic children / Norzehan Sakamat, Siti Nabilah Sabri and Norizan Mat Diah - Sakamat, Norzehan; Sabri, Siti Nabilah; Mat Diah, Norizan (Research Management Institute (RMI), 2017)
Storytelling is considered as an interactive social arts that uses word and gestures to reveal the elements and images of a story while engaging the listener's imagination. Multimedia based digital storytelling learning approach provides interesting, interactive, engaging and multisensory learning experience to children. Children explore new experience and scenarios as new stories are being told. This study concentrates on determining the best combination of elementsfor designing effective digital storytelling applications specifically for the usage of dyslexic children. Dyslexic children are known to have a common learning difficulty that can cause problems with reading, writing, spelling and comprehension. These applications are design with the objective to help in improving dyslexic children ability in readings and comprehensions. Four elements were derived from extensive literature studies. The elements are multimedia components, multi-sensory instructional approach, emotional design and games design. The relationship among all the elements were determine and described in details as it will be used to contribute to the design and development of the application in further works. The strength of this study is it models the combinations of technology, psychology and instructional approach as a support componentsfor developing an effective digitalstory telling learning application for dyslexic children.